Pembinaan dalam Jambore Pemuda Remaja Gereja Kristen Kerasulan Indonesia 2023 - Prianto, Robi; Sihombing, Aeron Frior; Surtinah, Surtinah; Tampubolon, Yohanes Hasiholan (Edumedia Solution, 2024)
This Community Service Program aims to help enhance the faith of young people in facing the challenges of modern life and the surrounding culture. The guidance includes teaching on Christian doctrines, basic concepts of the Christian faith, and the application of teachings in the context of modern life. The methods used in the mentoring activities are lectures and question-and-answer sessions. The activities are conducted on Saturday, July 01, 2023, at the GKKI Kopeng Branch, carried out in two sessions. The mentoring process is carried out through three stages, including preparation, implementation, and evaluation. In the preparation stage, the team communicates with the GKKI Synod chairperson and the Jamboree Committee. Additionally, it is crucial for young people to receive social support and spiritual guidance from church leaders and peer mentors. The development of an inclusive church community that is friendly to young people and relevant to their needs is also an essential step in supporting the spiritual growth of the church's youth. This article is expected to provide insights into the importance of mentoring in strengthening the faith of youth in the church.